Strategic Orientation On Performance: The Resource Based View Theory Approach - Raymond Dionysus; Agus Zainul Arifin (Jurnal Akuntansi, 2020)
This study aims to verify of the relationship between Entrepreneurship Orientation and Market Orientation to Small and Medium Enterprise (SME) Performance, using the Resource Based View (RBV) theory approach. The research object used was SME entrepreneurs in DKI Jakarta. This research uses a quantitative research design. The data used in this research consists of primary data and collected through Google Forms, which are distributed online. The amount of data collected was 190 samples. The collected data will be analyzed using SEM-PLS Version 3.3.2. Statistical analysis test the outer and inner models. The results obtained indicate that Entrepreneurship Orientation plays a role in SME Performance, and Market Orientation does not affect SME Performance. The implication of this research shows that the Resource Based View theory is right to explain the relationship between Entrepreneurial Orientation and SME Performance because SME performance will be better if it has Entrepreneurial Orientation.